722. Parasitic and Non-Parasitic Causes of Eosinophilia in Children Presenting to a Tertiary Care Center in the United States. (4th December 2021) - Ness, Tara; Erickson, Timothy; Diaz, Veronica; Hajjar, Joud; Anvari, Sara; Weatherhead, Jill E
Abstract: Background: Peripheral eosinophilia can be caused by many underlying conditions, including infectious pathogens, allergic disorders, neoplastic disorders, and immunological disorders. However, uncovering the cause of eosinophilia in children can be challenging due to the wide differential diagnosis. Methods: To identify causes and risk factors of eosinophilia in children, we performed a retrospective chart review of children presenting to Texas Children's Hospital in Houston, TX with peripheral eosinophilia from January 1, 2011 to December 31, 2019. Eosinophilia was classified as mild (absolute eosinophilia count or AEC >500 and < 1500), moderate (AEC >1500 and < 5000) and severe (AEC > 5000). Demographic information in addition to travel history, co-morbid conditions, and diagnostic workup were collected. Results: A total of 773 patients under 18 years of age were evaluated. The most common cause of eosinophilia in children was atopy (N=343, 44%), followed by eosinophilia of unknown etiology (N=227, 29%). Infectious pathogens were the etiology in 8% of cases of which all were parasitic pathogens. Helminthic (n=48, 79% of parasitic diseases in total) pathogens were more common than protozoan (n=13, 21% of parasitic diseases in total) and patients with parasitic infections had higher median eosinophilia compared to other subgroups (median = 1661, range 512-17, 501) with the majority having moderate to severe eosinophilia (57%). The most common helminth was Toxocara (n=31), followed by Strongyloides (n=15 ), and, more rarely, pinworms (n=4). The most common protozoa identified was Dientamoeba fragilis (n=9), followed by Giardia species (n=5), Endolimax nana (n=4), Blastocystis species (n=3), and Iodamoeba butschlii (n=1). Many unknown cases had limited workup that did not include investigations for common parasites. Conclusion: While atopy and unknown etiology were the most common diagnoses for children presenting with eosinophilia, parasites were relatively common and should be considered in the differential when investigating etiologies for peripheral eosinophilia. Disclosures: Joud Hajjar, MD, MS, Baxalta (Grant/Research Support)Horizon (Advisor or Review Panel member)Pharming (Advisor or Review Panel member)